Medievalism in nineteenth-century Belgium : the 1848 monument to Godfrey of Bouillon. - John, Simon (Simon A.) (The Boydell Press, 2023)
Offers new insights into the political and modern uses of public monuments devoted to figures from the past and the role of historical culture in the creation of national identity.